A scientific analysis on the water levels of Lake Beysehir and drought conditions in the area - Erkoc, M. H. (IST NAZIONALE DI OCEANOGRAFIA E DI GEOFISICA, 2023)
Lake Beysehir is a crucial water resource for its region; however, its water level has visibly decreased over the past decade, thus posing a threat to the lake's sustainability. This study aims to investigate the causes behind this phenomenon and its impact on the lake surface area. To achieve this, the study uses monthly lake water level data from the Copernicus Land Service, meteorological data, and Sentinel-2 high-resolution satellite images. From these data sets, four indices are calculated for the period between 2015 and 2020: the Standardised Precipitation Index (SPI), Standardised Precipitation Evapotranspiration Index (SPEI), Normalised Difference Water Index (NDWI), and Modified Normalised Difference Water Index (MNDWI). The results of the analysis indicate a significant decrease in the lake water level over the past ten years, along with mild, extreme, and severe drought conditions. Additionally, the Sentinel-2 images show a gradual reduction in the lake surface area during the same period. The study underscores the urgent need to address the impacts of climate change on freshwater resources to ensure the sustainability of Lake Beysehir and its surroundings.
Keywords: INDEX NDWI; URMIA; Geochemistry & Geophysics